A new texturing technique for silicon solar cells using gas phase etching - Shaw, EC (2022)
Solar energy is vital to combatting climate change. However, not all incident photons can transmit into a typical solar cell for electricity generation, a portion of the photons are lost to front surface reflectance. By changing the front surface texture of typical solar cells from microscale to nanoscale, the solar cell front surface reflectance (at wavelengths of interest), can be reduced to almost 0%. Such a change would increase the number of photons available in the solar cell for electricity generation. Despite the excellent optical properties nano-textures can offer, all current industrially relevant nanoscale texturing methods have drawbacks that prevent them from gaining a significant market share. This thesis explores texturing in the gas-phase to overcome the drawbacks of other nanoscale texturing techniques, whilst still providing exceptional optical properties to improve solar cell efficiency.